Integrasi Six Sigma dan FMEA (Failure Mode And Effect Analysis) untuk Peningkatan Kualitas Produk Koran (Studi Kasus: PT. ABC Manufacturing – Sidoarjo, Jawa Timur – Indonesia) - Muchammad Alfan Lutfianto; Rony Prabowo (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
PT. ABC is a subsidiary of the JawaPos Group, founded in 1996, and is one of the companies in East Java engaged in printing and packaging. The products produced include magazines, books and newspapers. Of all the products that the company has created, one of the biggest defects is found in newspaper products, which is 4% of the average newspaper product production of 806.59 copies and produces a moderate defect of 22,743 copies in 2019. In this research, the method applied is the Six Sigma method and Failure Mode and Effect Analysis (FMEA), by implementing and carrying out the stages in the Six Sigma method, namely DMAIC (Define, Measure, Analyze, and Control). From this research, the results obtained are that the company has several newspaper product defects of 181,943 copies consisting of several types of product defects, including damp paper, blurred colours, shaded printing, asymmetrical printing, and running printing. The company is currently at the 4.04 sigma level, so corrective actions need to be taken to achieve six sigma levels. By applying the Failure Mode and Effects Analysis (FMEA) method, it can be seen that the biggest and most frequent product defect is a blurred colour defect. So that the recommended alternative solution for repairs is to check the ink and replace the ink with standard ink or have a lower density, perform regular and systematic machine checks, and provide further guidance on newspaper printing production standards to all operators involved work.